2011
DOI: 10.1590/s0100-06832011000500037
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties related to acidity under successive pig slurry application

Abstract: SUMMARYLong-term applications induced an increase in organic matter in the deeper layers. However, the effect of this residue on the potential CEC was less significant and restricted to the surface layers.Index terms: water pH, base saturation, Al saturation, soil organic matter, organic waste. 0-2, 2-4, 4-6, 6-8, 8-10, 10-12, 12-14, 14-16, 16-18, 18-20, 20-25, 25-30, 30-35, 35-40, 40-50 e 50-60 RESUMO: ATRIBUTOS QUÍMICOS RELACIONADOS A ACIDEZ EM SOLO COM SUCESSIVAS APLICAÇÕES DE DEJETO LÍQUIDO DE SUÍNOS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 20 publications
(19 reference statements)
9
58
2
8
Order By: Relevance
“…They also found no significant changes in other properties related to soil acidity. However, different results were found by Lourenzi et al (2011) in an Ultisol soil, where an increase in pH in water was found in the surface layer after pig slurry applications.…”
Section: Soil Chemical Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…They also found no significant changes in other properties related to soil acidity. However, different results were found by Lourenzi et al (2011) in an Ultisol soil, where an increase in pH in water was found in the surface layer after pig slurry applications.…”
Section: Soil Chemical Propertiesmentioning
confidence: 72%
“…However, Lourenzi et al (2011) found different results, with increasing organic matter in deeper soil layers after pig slurry application.…”
Section: Soil Chemical Propertiesmentioning
confidence: 91%
“…Thus, nutrient contents in the soil are expected to increase over the years (Mcdowell et al, 2001;Basso et al, 2005;Gatiboni et al, 2008;Ceretta et al, 2010a,b;Girotto et al, 2010). The chemical properties related to soil acidity are also expected to change, e.g., with increases in soil pH and base saturation, as well as a decrease in aluminum saturation (Ceretta et al, 2003;Lourenzi et al, 2011). Although there is abundant literature on the effects of pig slurry, no information was found about the effects of swine deep-litter on soil acidity parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a small soil contact area is expected, with a consequent delay in the microbial biomass activity, which may stimulate total organic carbon (TOC) accumulation (Ceretta et al, 2003;Adeli et al, 2008;Lourenzi et al, 2011), particularly in the surface layers. However, increases in TOC contents are mainly associated to the manure composition, application frequency and amount (Falleiro et al, 2003;Lourenzi et al, 2011). These changes can increase the soil cation exchange capacity (CEC) R. Bras.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation